PENGGUNAAN METODE PEMBELAJARAN OUTDOOR STUDY TERHADAP PEMAHAMAN KONSEP PELESTARIAN LINGKUNGAN HIDUP PESERTA DIDIK DI MTsN SINGAPARNA - Kurniangsih, Alien; Darsiharjo, Darsiharjo; Maryani, Enok (Jurnal Pendidikan Geografi Gea, 2015)
In an era of globalization of environmental sustainability issues into one focus of attention. All components agreed to lift the attitude and wisdom in the environment that need to transfer knowledge through educational institutions. Understanding the form of the values in the learning process needs to be passed on to each generation. On that basis, the study was conducted under the title "Influence of Outdoor Learning Method Study in Kampung Naga Against Environmental Conservation Concept Training Students of Class VIII MTsN Singaparna". The goal was to determine the students understanding of the concept of environmental conservation with learning methods Outdoors Study and as a source of learning is Kampung Naga in Tasikmalaya district. Selection of Kampung Naga as a place to do experiments because Kampung Naga is one example of the village managed to preserve the natural environment. The method used in this quasi-experimental study with pretest-posttest Equivalent Groups. The study sample consisted of two classes of class VIII B as a class experiment by utilizing Kampung Naga through learning methods Outdoors Study and VIII A as a control class by utilizing Kampung Naga through learning methods Gallery Walk.Â